Hypothalamic Orexin-A Neurons Are Involved in the Response of the Brain Stress System to Morphine Withdrawal - Laorden, M. Luisa; Ferenczi, Szilamér; Pintér-Kübler, Bernadett; González-Martín, Laura L.; Lasheras, M. Carmen; Kovács, Krisztina J.; Milanés, M. Victoria; Núñez, Cristina (PLOS ONE, 2012)
Both the hypothalamus-pituitary-adrenal (HPA) axis and the extrahypothalamic brain stress system are key elements of the neural circuitry that regulates the negative states during abstinence from chronic drug exposure. Orexins have recently been hypothesized to modulate the extended amygdala and to contribute to the negative emotional state associated with dependence. This study examined the impact of chronic morphine and withdrawal on the lateral hypothalamic (LH) orexin A (OXA) gene expression and activity as well as OXA involvement in the brain stress response to morphine abstinence. Male Wistar rats received chronic morphine followed by naloxone to precipitate withdrawal. The selective OX1R antagonist SB334867 was used to examine whether orexins' activity is related to somatic symptoms of opiate withdrawal and alterations in HPA axis and extended amygdala in rats dependent on morphine. OXA mRNA was induced in the hypothalamus during morphine withdrawal, which was accompanied by activation of OXA neurons in the LH. Importantly, SB334867 attenuated the somatic symptoms of withdrawal, and reduced morphine withdrawal-induced c-Fos expression in the nucleus accumbens (NAc) shell, bed nucleus of stria terminalis, central amygdala and hypothalamic paraventricular nucleus, but did not modify the HPA axis activity. These results highlight a critical role of OXA signalling, via OX1R, in activation of brain stress system to morphine withdrawal and suggest that all orexinergic subpopulations in the lateral hypothalamic area contribute in this response.